179k views
0 votes
An equation of the line tangent to y=x3+3x2+2 at its point of inflection is

A. y=−6x−6y is equal to negative 6 x minus 6

B. y=−3x+1y is equal to negative 3 x plus 1

C. y=2x+10y is equal to 2 x plus 10

D. y=3x−1

User Gameweld
by
4.9k points

1 Answer

2 votes

Answer:


y = -3x +1

Step-by-step explanation:

Given


y = x^3 + 3x^2 + 2

Required

Determine the equation at the point of inflection

The point of inflection of a curve is the point where the second derivative is 0.

So:


y = x^3 + 3x^2 + 2

First derivative is:


y' = 3x^2 + 6x

Second derivative:


y

Equate to 0


6x + 6 = 0

Solve for x


6x = -6


x = -1

Next, we calculate the slope (m) of the point using the first derivative.

Substitute -1 for x in
y' = 3x^2 + 6x


m = 3*-1^2 + 6 * -1


m = 3*1 - 6


m = 3 - 6


m = -3

To get the y equivalent;

Substitute
x = -1 in
y = x^3 + 3x^2 + 2


y = (-1)^3 + 3(-1)^2 + 2


y = -1 + 3+ 2


y = 4

Lastly, we calculate the line equation using:


y - y_1 =m(x- x_1)

Where


x = -1 and
y = 4


m = -3

So, we have:


y - 4 = -3(x -(-1))


y - 4 = -3(x +1)


y - 4 = -3x -3

Make y the subject


y = -3x -3 +4


y = -3x +1

Hence, the equation is:
y = -3x +1

User Rob J
by
5.2k points